AN INVESTIGATION OF STROKE AWARENESS AND APPROACHES TO STROKE PATIENTS IN INTERN PHYSICIANS AND NURSES - Mustafa Bayraktar; Mehmet Nuri Koçak; Erdal Tekin; Suat Sincan; Hüseyin Laçin (İstanbul Tıp Fakültesi Dergisi)
Objective: Ischemic stroke is an emergency, requires prompt and accurate diagnosis to determine the need for urgent hospitalization and specific treatment. This study investigates our hospital’s nurses’ and intern physicians’ knowledge and awareness of ischemic stroke. Method: A questionnaire consisting of 10 questions evaluating stroke awareness, the symptoms, first intervention, transportation and first treatment approaches, was completed by 110 volunteer participants (55 nurses and 55 intern physicians). Results: The rate of stroke awareness of nurses was 51.1%. In terms of knowledge concerning the first assessment of the patients, it was a remarkable result that the detection of hypoglycemia, opening two vascular access routes and not interfering with hypertension scored a very low rate of 20.9% in nurses. The correct answer rate of intern physicians to the questionnaire was 77.6%. Statistically, there was no significance between the responses of the nurses and the intern physicians in terms of age, occupational duration, stroke intervention and stroke training history (p>0.05). Conclusion: All healthcare professionals should be trained in the diagnosis of acute ischemic stroke, the necessity of measuring fingertip blood glucose, not to interfere with hypertension and understanding the value of thrombolytic treatment in the first 4.5 hours.